The Dynamic Relationship between Macroeconomy and Stock Market in China: Evidence from Bayesian Network. (16th December 2021) - Liu, Yue; Feng, Haoyuan; Guo, Kun
Abstract : As the most important component of the capital market, the stock market has always been regarded as the "barometer" of the macroeconomy. However, many researchers have found that the stock market and macroeconomy are operating separately. This paper uses the dynamic Bayesian network method to study the dynamic relationship between the Chinese macroeconomic system and the stock market. The study found that the correlation between the macroeconomic system and the stock market is not consistent in different time periods. For most of the time, the stock system and the macroeconomic system are relatively independent. However, several macroeconomic factors such as Purchase Management Index could affect the stock market through some industries. A conclusion is drawn that the "barometer" function of the stock market is weak and easy to be damaged by factors such as the irrational sentiment of investors.